Development of virus-like particles with inbuilt immunostimulatory properties as vaccine candidates - Collett, Simon; Earnest, Linda; Carrera Montoya, Julio; Edeling, Melissa A.; Yap, Ashley; Wong, Chinn Yi; Christiansen, Dale; Roberts, Jason; Mumford, Jamie; Lecouturier, Valerie; Pavot, Vincent; Marco, Sergio; et al. (Frontiers in Microbiology, 2023)
Abstract The development of virus-like particle (VLP) based vaccines for human papillomavirus, hepatitis B and hepatitis E viruses represented a breakthrough in vaccine development. However, for dengue and COVID-19, technical complications, such as an incomplete understanding of the requirements for protective immunity, but also limitations in processes to manufacture VLP vaccines for enveloped viruses to large scale, have hampered VLP vaccine development. Selecting the right adjuvant is also an important consideration to ensure that a VLP vaccine induces protective antibody and T cell responses. For diseases like COVID-19 and dengue fever caused by RNA viruses that exist as families of viral variants with the potential to escape vaccine-induced immunity, the development of more efficacious vaccines is also necessary. Here, we describe the development and characterisation of novel VLP vaccine candidates using SARS-CoV-2 and dengue virus (DENV), containing the major viral structural proteins, as protypes for a novel approach to produce VLP vaccines. The VLPs were characterised by Western immunoblot, enzyme immunoassay, electron and atomic force microscopy, and in vitro and in vivo immunogenicity studies. Microscopy techniques showed proteins self-assemble to form VLPs authentic to native viruses. The inclusion of the glycolipid adjuvant, -galactosylceramide (-GalCer) in the vaccine formulation led to high levels of natural killer T (NKT) cell stimulation in vitro, and strong antibody and memory CD8+ T cell responses in vivo, demonstrated with SARS-CoV-2, hepatitis C virus (HCV) and DEN VLPs. This study shows our unique vaccine formulation presents a promising, and much needed, new vaccine platform in the fight against infections caused by enveloped RNA viruses.